HUBUNGAN PERHATIAN ORANGTUA DENGAN MOTIVASI BELAJAR SISWA DALAM MENGERJAKAN TUGAS-TUGAS SEKOLAH - Febriany, Rani; Yusri, Yusri (Universitas Negeri Padang, 2013)
Parents are factors influencing students motivation in learning, them motivation in school work. In fact many students show low motivation in school work is influence by parents aconcern. The study aims to reveal the relationship of parents concern to student motivation homework. Type a descriptive correlational study with findings that parents concern is quite, student motivation homework is quite high and there is a significant relationship between parents' attention to student motivation homework.